Cultural tourism an anglo-ethnocentism: discovering the others through consumption - Korstanje, Maximiliano E. (Revista Hipótese, 2017)
The present essay review centres a strong discussion on the role of cultural tourism subordinating aboriginal groups to the interests of white status quo. Though beyond the promise of a better world, cultural tourism emulates, there is further poverty, we adopt a more radical discourse which unveil the perverse core of heritage, which was a cultural project of colonial order to discipline natives. The main thesis is that cultural tourism is framed under a logic of expropriation stimulated by global capitalism, to perpetuate the centre-periphery dependence. While during the times of colony, the other should be discovered to be disciplined or even in other cases enslaved, in modern times, the other is gazed to internalize “a role or a biased image” that highlights the Western Supremacy over other local values.
Keywords: Globalization; Tourism; Cultural tourism; Consumption; Aborigines